1999
DOI: 10.1002/(sici)1097-4644(19990915)74:4<638::aid-jcb13>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of tunicamycin to cultured brain neurons: Ultrastructure of the degenerating neurons

Abstract: Our previous study has shown that tunicamycin irreversibly downregulates the expression of GABA A R and causes cell death in cultured brain neurons by biochemical and light microscopic methods. In this study, we examined mechanisms underlying the degeneration of the neurons mainly employing electron microscopic analysis. Cultured neurons derived from embryonic chicken brains were incubated with 5 µg/ml of tunicamycin (TM) for 24 h, followed by continual incubation or removal of TM for additional 3 h or 24 h. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…2B, insets). The periphery of these structures contained both mutant PLPmh and calnexin, resembling the distended ER that has been observed under conditions of chronic ER stress (Alvarez et al, 1999;Dalal et al, 2004;Lass et al, 2008;Lin et al, 1999). The milddisease-associated mutants W162L and G245A were also present A twodimensional model of PLP topology illustrating the four TM domains, cytosolic N-and C-termini, palmitoylation sites (squiggles), and disulphide bonds (straight lines).…”
Section: Retention Of Disease-associated Plp Mutants By the Er Qualitmentioning
confidence: 80%
“…2B, insets). The periphery of these structures contained both mutant PLPmh and calnexin, resembling the distended ER that has been observed under conditions of chronic ER stress (Alvarez et al, 1999;Dalal et al, 2004;Lass et al, 2008;Lin et al, 1999). The milddisease-associated mutants W162L and G245A were also present A twodimensional model of PLP topology illustrating the four TM domains, cytosolic N-and C-termini, palmitoylation sites (squiggles), and disulphide bonds (straight lines).…”
Section: Retention Of Disease-associated Plp Mutants By the Er Qualitmentioning
confidence: 80%
“…Such disorganization could result in changes in the ratio, size, and shape of ER cisternae and tubules. Morphologically similar swelling is seen in a few pathological conditions, including intoxication with the pore forming toxin aerolysin (Abrami et al, 1998), prolonged exposure of cells to BFA (Alvarez and Sztul, 1999), and treatment of neurons with tunicamycin (Lin et al, 1999). Further understanding of the events that lead to ER dilation will shed light on how p97 participates in ER homeostasis.…”
Section: Nsf and Membrane Fusionmentioning
confidence: 88%
“…Alpha-mannosidase, a key enzyme converting precursor high-mannose-type N-glycan to matured complex-type structure, contributes to the establishment of an equitable glycoprotein quality control standard, by which the efficiency of Asn-linked glycoprotein conformational maturation results in dislocation of misfolded glycoproteins into the cytosol where proteins are degraded in the proteasome and maintain the homeostasis of ER [2] . Lin et al [24] cultured neurons derived from embryonic chicken brains with tunicamycin (TM), an inhibitor of N-linked glycosylation, and found that the light neurons resembled necrotic cells, but the dense neurons exhibited distinct morphological features of necrosis and apoptosis, indicating that TM has an irreversible toxicity to the neurons and a different mechanism underlying neuron death.…”
Section: Treatmentmentioning
confidence: 99%